A combined experimental and modelling investigation of an overground compressed-air energy storage system with a reversible liquid-piston gas compressor/expander. (1st October 2021) - Khaljani, M.; Harrison, J.; Surplus, D.; Murphy, A.; Sapin, P.; Markides, C.N.; Mahmoudi, Y.
Highlights: CAES systems with reversible liquid-piston gas compressor/expander is presented. Experimental and thermodynamic analyses are conducted for five system configurations. The CAESPCM&plate configuration shows the highest roundtrip efficiency of 63%. The CAESPCM&plate system has the shortest payback period of 7 years. For a 20-year lifetime, the CAESPCM&plate system reduces CO2 emission by 51 tonnes. Abstract: We consider a small-scale overground compressed-air energy storage (CAES) system intended for use in micro-grid power networks. This work goes beyond previous efforts in the literature by developing and showing results from a first-of-a-kind small-scale (20 kWh) near-isothermal CAES system employing a novel, reversible liquid-piston gas compressor and expander (LPGC/E). Additionally, we extend our study to assessments, for the first time, of the economic and environmental characteristics of these small-scale overground CAES systems through a combination of experimental, thermodynamic, technoeconomic and environmental analyses. Five system configurations are considered: (1) CAESbase, which is the base-case system; (2) CAESplate, in which parallel plates are inserted into the LPGC/E as a heat exchanger for achieving near-isothermal compression and expansion; (3) CAESPCM, in which a phase change material (PCM) is employed to store thermal energy from the compressed air during charging that is later recovered during discharge; (4) CAESPCM&plate, which is a combination of the CAESplate and CAESPCM arrangements; and (5) CAESheater, in which a heater is utilised instead of the PCM to preheat the compressed air during discharge. Data for the validation of a computational design tool based on which the assessments were performed were obtained from a prototype of the CAESbase system. Results show that the CAESPCM&plate system exhibits the highest roundtrip efficiency of 63% and the shortest payback period of 7 years; the latter with the inclusion of governmental incentives and an electricity smart export guarantee (SEG) support rate of 5.5 p/kWh (6.8 ¢/kWh). The CAESPCM&plate system is found to be cost-effective even without incentives, with a payback period of 10 years. This system is also associated with 71 tonnes of fuel consumption savings and reduced CO2 emissions amounting to 51 tonnes over a lifetime of 20 years.